(3cJGH aj GdCOHs
(3ChdgG (B:s
(3CeG HYO, aEf GdYde CTQa GdPNGFQ, hgh ChSY ef GdHMQ GdRGNQ s
(3BNQgG (B:s
(3ebGe jTJed Ydi eG PcQg GdMcje aj GdHdM s
(3jTJed Ydi NeSI YTQ HGHkGs
(3cd HGH aj YOI aUhd aj ehVhYGJ TJis
(3hChQGbgG eVWQHI GdJQJjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B140 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs